Spectrometer‐free Optical Hydrogen Sensing Based on Fano‐like Spatial Distribution of Transmission in a Metal−Insulator−Metal Plasmonic Doppler Grating. Issue 22 (12th September 2021) - Chen, Yi‐Ju; Lin, Fan‐Cheng; Singh, Ankit Kumar; Ouyang, Lei; Huang, Jer‐Shing
Abstract: Optical nanosensors are promising for hydrogen sensing because they are small, free from spark generation, and feasible for remote optical readout. Conventional optical nanosensors require broadband excitation and spectrometers, rendering the devices bulky and complex. An alternative is spatial intensity‐based optical sensing, which only requires an imaging system and a smartly designed platform to report the spatial distribution of analytical optical signals. Here, a spatial intensity‐based hydrogen sensing platform is presented based on Fano‐like spatial distribution of the transmission in a Pd‐Al2 O3 ‐Au metal‐insulator‐metal plasmonic Doppler grating (MIM‐PDG). The MIM‐PDG manifests the Fano resonance as an asymmetric spatial transmission intensity profile. The absorption of hydrogen changes the spatial Fano‐like transmission profiles, which can be analyzed with a "spatial" Fano resonance model and the extracted Fano resonance parameters can be used to establish analytical calibration lines. While gratings sensitive to hydrogen absorption are suitable for hydrogen sensing, hydrogen insensitive gratings are also found, which provide an unperturbed reference signal and may find applications in nanophotonic devices that require a stable optical response under fluctuating hydrogen atmosphere. The MIM‐PDG platform is a spectrometer‐free and intensity‐based optical sensor that requires only an imaging system, making it promising for cellphone‐based optical sensing applications. Abstract : An azimuthally chirped Pd‐Al2 O3 ‐Au metal‐insulator‐metal plasmonic Doppler grating (MIM‐PDG) is developed for spectrometer‐free optical hydrogen sensing. The single‐color transmission intensity profile exhibits a spatial Fano profile, offering azimuthal angle‐dependent hydrogen uptake sensitivity. The platform is multifunctional for various applications as it simultaneously provides plasmonic gratings sensitive and resistive to the change of environmental hydrogen concentration.